Adjunctive effect of the colloidal silver ions solution in the treatment of chronic periodontal disease: a preliminary clinical study - Kovačević, Vladan M.; Daković, Dragana R.; Bokonjić, Dubravko R (Vojnosanitetski pregled, 2021)
Background/Aim. Bacteria play the most important role in the development of periodontitis and chlorhexidine (CHX) is a “gold standard” in its treatment. Silver ions are also strong antiseptics, being used in dentistry for a long time. Therefore, the aim of this study was to compare the efficacy of CHX and colloidal silver ions solution (SSI) in the treatment of patients with chronic periodontitis. The additional aim was to ascertain silver ions, tolerability and efficacy comparing to CHX. Methods. Twenty-nine examinees of both sexes (the average age 50.6) participated in this study and were divided into two groups. The patients in the first group (n = 15) suffering from a generalized moderate chronic periodontitis, after scaling and root planning (SRP), were treated by rinsing of periodontal pockets with 0.2% solution of CHX. The patients of the second group (n = 14), in addition to the treatment of periodontal pockets, were treated with a 5 mg/mL colloidal SSI. Results. During the periodontal treatment, the mean values of all clinical parameters (except clinical attachment loss – CAL), in the both groups of patients were statistically significantly lower (p < 0.001) in relation to the initial values. The greater reduction of periodontal bleeching on probing (BOP) depth after one month was found in the SSI treated group (0.97 mm) in relation to the CHX group (0.65 mm). The local application of CHX and SSI led to statistically significant reduction of gingival parameters (gingival index – GI and BOP) in the groups after the treatment (GI for 0.65 and 0.87; BOP for 0.31 and 0.33, respectively). Conclusion. The results of our study showed that colloidal SSI was at least equally effective in the treatment of patients with periodontal disease as the solution of CHX. Additionally, the SSI is simple for use which speaks in favor of its more extensive use in dentistry including chronic periodontal disease.
Keywords: periodontal diseases; periodontal index; chlorhexidine; silver.